“If U Don’t Pay they will Share the Pics”: Exploring Sextortion in the Context of Romance Fraud - Cross, Cassandra (Victims & offenders, 2023)
Romance fraud involves the guise of a perceived genuine relationship to gain a financial reward. While those who commit these crimes employ a variety of techniques, emerging evidence suggests the use of sextortion to financially gain from victims. To date, sextortion has been explored generally in the image-based sexual abuse and sexual violence literature but not in the context of romance fraud. This article explores reports of 258 individuals who made a complaint to Scamwatch (Australian online fraud reporting portal) about romance fraud, captured between July 2018 and July 2019 (inclusive). Each of these complaints directly references the use of sextortion, through a threat to expose an intimate image or recording in response to a monetary request. Using an established cyber sextortion typology, this article applies these categories in the context of romance fraud to determine if there is consistency in the use of this technique, or whether its use in the context of romance fraud is unique.